2021
DOI: 10.1063/5.0034995
|View full text |Cite
|
Sign up to set email alerts
|

Space charge limited current for bipolar flow with uniform initial velocity

Abstract: The characteristics of space charge limited (SCL) bipolar flow in a planar ion diode with uniform initial velocity are studied in terms of the potential distribution. As a negative potential minimum occurs, a general expression for the limiting current density as a function of the normalized initial kinetic energy of electron αe and ion αi, normalized potential minimum αm, and ratio of ion current density to electron current density q is shown to be given by Je=JCL[Γ(αe,αi,αm,q)]2 in the form of a definite int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Also, it is observed that when the injection current is larger, the average current density is even going to decrease under the stronger impact of the self-induced electric field which pulls the electrons back, as compared between the blue line and the black line shown in Fig. 2, and we term it as the over-SCL effect, which is also demonstrated by Zhu et al [46].…”
Section: A the Over-scl Effectsupporting
confidence: 53%
See 1 more Smart Citation
“…Also, it is observed that when the injection current is larger, the average current density is even going to decrease under the stronger impact of the self-induced electric field which pulls the electrons back, as compared between the blue line and the black line shown in Fig. 2, and we term it as the over-SCL effect, which is also demonstrated by Zhu et al [46].…”
Section: A the Over-scl Effectsupporting
confidence: 53%
“…As shown in Fig. 2, larger injection current will decrease the transported current at some inflection point and the point is easier to obtain [46]. Thus, in this article, we choose the maximal transported current density as the value of interest to study.…”
Section: Combined Effect Of Electron Emission Temporal Profile and In...mentioning
confidence: 99%
“…where η * = β 2 + y * . Similar to appendix A, equation (41) provides an expression allowing us to replace α in favor of η * . For y * = 0 (which gives η * = β), equation ( 41) reduces to α = α tr as expected since the location of the local potential minimum/maximum is exactly at the injection electrode.…”
Section: Discussionmentioning
confidence: 99%
“…Here the body of work is extensive [35], and includes the derivation of the simple SCL limit (i.e. the famous Child-Langmuir law) [22,36], the effect of a finite particle injection velocity [37][38][39][40][41], 2D and 3D geometries (including cylindrically and spherically symmetric systems) [23,[42][43][44][45][46], and even extensions to quantum and relativistic regimes [47][48][49].…”
Section: Introductionmentioning
confidence: 99%
“…Since J Jaffé > J B , we define this as the SCLC. Other studies have looked at other additional velocity cases such as thermal distributions [55] and bipolar flows [56], but we will only be analyzing the case of monoenergetically emitted electrons.…”
Section: Introductionmentioning
confidence: 99%